Film-forming material for lithography, film-forming composition for lithography, underlayer film for lithography, and pattern forming method
Patent Information
- Application Number
- JP2021539247
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-09
- Filing Date
- 2020-08-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-08-06
AI Technical Summary
【0042】 本発明によれば、湿式プロセスが適用可能であり、エッチング耐性に優れるフォトレジスト下層膜を形成するために有用な、リソグラフィー用膜形成材料、該材料を含有するリソグラフィー用膜形成用組成物、並びに、該組成物を用いたリソグラフィー用下層膜及びパターン形成方法を提供することができる。
Smart Images

Figure 0007643336000001 
Figure 0007643336000002 
Figure 0007643336000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a film-forming material for lithography, a film-forming composition for lithography containing the material, an underlayer film for lithography formed using the composition, and a pattern formation method (e.g., a resist pattern method or a circuit pattern method) using the composition. [Background technology]
[0002] In the manufacture of semiconductor devices, microfabrication is carried out by lithography using photoresist materials. In recent years, with the increasing integration and speed of LSIs, further miniaturization by pattern rules is required. In the lithography using light exposure, which is currently used as a general-purpose technology, the essential resolution limit derived from the wavelength of the light source is approaching.
[0003] The light source for lithography used in forming a resist pattern has been shortened from KrF excimer laser (248 nm) to ArF excimer laser (193 nm). However, as the resist pattern becomes finer, problems such as resolution problems or the resist pattern collapsing after development arise, so that it is desirable to make the resist thinner. However, simply making the resist thinner makes it difficult to obtain a resist pattern with a film thickness sufficient for substrate processing. Therefore, a process has become necessary in which not only the resist pattern but also a resist underlayer film is formed between the resist and the semiconductor substrate to be processed, and this resist underlayer film also functions as a mask during substrate processing.
[0004] Currently, various resist underlayer films for such processes are known. For example, unlike conventional resist underlayer films with a high etching rate, a material for forming an underlayer film for multilayer resist processes containing a resin component having at least a substituent that generates a sulfonic acid residue by detaching an end group when a certain energy is applied and a solvent has been proposed as a material for realizing a resist underlayer film for lithography having a dry etching rate selectivity close to that of a resist (see Patent Document 1). In addition, a resist underlayer film material containing a polymer having a specific repeating unit has been proposed as a material for realizing a resist underlayer film for lithography having a dry etching rate selectivity smaller than that of a resist (see Patent Document 2). Furthermore, a resist underlayer film material containing a polymer obtained by copolymerizing a repeating unit of acenaphthylenes and a repeating unit having a substituted or unsubstituted hydroxyl group has been proposed as a material for realizing a resist underlayer film for lithography having a dry etching rate selectivity smaller than that of a semiconductor substrate (see Patent Document 3).
[0005] On the other hand, as a material having high etching resistance in this type of resist underlayer film, an amorphous carbon underlayer film formed by CVD using methane gas, ethane gas, acetylene gas, or the like as a raw material is well known.
[0006] The present inventors have also proposed an underlayer film-forming composition for lithography that contains a naphthalene formaldehyde polymer containing specific structural units and an organic solvent, as a material that has excellent optical properties and etching resistance, is soluble in a solvent, and is applicable to wet processes (see Patent Documents 4 and 5).
[0007] As for the method of forming the intermediate layer used in forming the resist underlayer film in the three-layer process, for example, a method of forming a silicon nitride film (see Patent Document 6) and a method of forming a silicon nitride film by CVD (see Patent Document 7) are known. In addition, as the intermediate layer material for the three-layer process, a material containing a silsesquioxane-based silicon compound is known (see Patent Documents 8 and 9). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2004-177668 A [Patent Document 2] JP 2004-271838 A [Patent Document 3] JP 2005-250434 A [Patent Document 4] International Publication No. 2009 / 072465 [Patent Document 5] International Publication No. 2011 / 034062 [Patent Document 6] JP 2002-334869 A [Patent Document 7] International Publication No. 2004 / 066377 [Patent Document 8] JP 2007-226170 A [Patent Document 9] JP 2007-226204 A Summary of the Invention [Problem to be solved by the invention]
[0009] As described above, numerous film-forming materials for lithography have been proposed to date, but none of them have both high solvent solubility that allows the use of wet processes such as spin coating and screen printing, and high levels of etching resistance, and the development of new materials is therefore required.
[0010] The present invention has been made in consideration of the above-mentioned problems, and an object of the present invention is to provide a film-forming material for lithography, which is useful for forming a photoresist underlayer film to which a wet process can be applied and which has excellent etching resistance, a film-forming composition for lithography containing the material, and an underlayer film for lithography and a pattern formation method using the composition. [Means for solving the problem]
[0011] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by using a compound having a specific structure, and have completed the present invention. That is, the present invention is as follows. [1] A group of the following formula (0):
[0012] [ka]
[0013] (In formula (0), R 01 , R 02 , R 03 are each independently a hydrogen atom, a linear or branched alkyl group having 1 to 18 carbon atoms, a cyclic alkyl group having 3 to 18 carbon atoms, an aryl group having 6 to 18 carbon atoms, an aralkyl group having 7 to 30 carbon atoms, or an alkylaryl group having 7 to 30 carbon atoms. A film-forming material for lithography, comprising a compound having the formula: [2] The film-forming material for lithography according to [1], wherein the compound having a group of the formula (0) is at least one selected from the group consisting of polyitaconimide compounds and itaconimide resins. [3] The film-forming material for lithography according to the above [1] or [2], wherein the compound having a group of the formula (0) is at least one selected from the group consisting of bisitaconimide compounds and addition polymerization type itaconimide resins. [4] The film-forming material for lithography according to the above [3], wherein the bisitaconimide compound is represented by the following formula (1):
[0014] [ka]
[0015] (In formula (1), R 01 , R 02 , R03 is defined as above, and Z is a single bond or a divalent group having 0 to 100 carbon atoms which may contain a heteroatom. [5A] The film-forming material for lithography according to the above [3] or [4], wherein the bisitaconimide compound is represented by the following formula (1A):
[0016] [ka]
[0017] (In formula (1A), R 01 , R 02 , R 03 is defined as above, X is independently a single bond, -O-, or -CH 2 -, -C(CH 3 ) 2 -, -CO-, -C(CF 3 ) 2 -, -CONH- or -COO-; A is a single bond, an oxygen atom, or a divalent hydrocarbon group having 1 to 80 carbon atoms which may contain a heteroatom; R 1 each independently represents a group having 0 to 30 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, Each m1 is independently an integer of 0 to 4. [5B] The film-forming material for lithography according to any one of [3] to [5A] above, wherein the bisitaconimide compound is represented by (1A) above. However, in formula (1A), R 01 , R 02 , R 03 is defined as above, X is independently a single bond, -O-, or -CH 2 -, -C(CH 3 ) 2 -, -CO-, -C(CF 3 ) 2 -, -CONH- or -COO-; A is a divalent hydrocarbon group having 1 to 80 carbon atoms which may contain a heteroatom, R 1 each independently represents a group having 0 to 30 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, Each m1 independently represents an integer of 0 to 4. [6A] The film-forming material for lithography according to any one of [3] to [5B] above, wherein the bisitaconimide compound is represented by (1A) above. However, in formula (1A), R 01 , R 02 , R 03 is defined as above, X is independently a single bond, -O-, or -CH 2 -, -C(CH 3 ) 2 -, -CO-, -C(CF 3 ) 2 -, -CONH- or -COO-; A is a single bond, an oxygen atom, -(CH 2 ) p -, -CH 2 C(CH 3 ) 2 CH 2 -, -(C(CH 3 ) 2 ) p -, -(O(CH 2 ) q ) p -, -(O(C 6 H 4 )) p - or any of the following groups:
[0018] [ka]
[0019] Y is a single bond, -O-, -CH 2 -, -C(CH 3 ) 2 -, -C(CF 3 ) 2 - or any of the following groups:
[0020] [ka]
[0021] R 1 each independently represents a group having 0 to 30 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, Each m1 independently represents an integer of 0 to 4, p is an integer from 1 to 20; Each q is independently an integer of 1 to 4. [6B] The film-forming material for lithography according to any one of [3] to [6A] above, wherein the bisitaconimide compound is represented by (1A) above. However, in formula (1A), R 01 , R 02 , R 03 is defined as above, X is independently a single bond, -O-, or -CH 2 -, -C(CH 3 ) 2 -, -CO-, -C(CF 3 ) 2 -, -CONH- or -COO-; A is -(CH 2 ) p -, -(C(CH 3 ) 2 ) p -, -(O(CH 2 ) q ) p -, -(O(C 6 H 4 )) p - or any of the following groups:
[0022] [ka]
[0023] Y is a single bond, -O-, -CH 2 -, -C(CH 3 )2 -, -C(CF 3 ) 2 - or any of the following groups:
[0024] [ka]
[0025] R 1 each independently represents a group having 0 to 30 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, Each m1 independently represents an integer of 0 to 4, p is an integer from 1 to 20; Each q is independently an integer of 1 to 4. [6-1A] The film-forming material for lithography according to any one of [3] to [6B] above, wherein the bisitaconimide compound is represented by (1A) above. However, in formula (1A), R 01 , R 02 , R 03 is defined as above, Each X is independently a single bond, -O-, -CO-, or -COO-; A is a single bond, an oxygen atom, -(CH 2 ) p1 -, -CH 2 C(CH 3 ) 2 CH 2 -, -(O(CH 2 ) q2 ) p3 - or any of the following groups:
[0026] [ka]
[0027] p1 is an integer from 1 to 10; q2 is an integer from 1 to 4; p3 is an integer from 1 to 20; Y is -C(CH 3 ) 2 -or-C(CF 3 ) 2 - and R 1 are each independently an alkyl group, Each m1 independently represents an integer of 0 to 4. [6-1B] The film-forming material for lithography according to any one of the above [3] to [6-1A], wherein the bisitaconimide compound is represented by the above (1A). However, in formula (1A), R 01 , R 02 , R 03 is defined as above, Each X is independently a single bond, -O-, -CO-, or -COO-; A is -(CH 2 ) p1 -, -(O(CH 2 ) q2 ) p3 or the structure
[0028] [ka]
[0029] p1 is an integer from 1 to 10; q2 is an integer from 1 to 4; p3 is an integer from 1 to 20; Y is -C(CH 3 ) 2 -or-C(CF 3 ) 2 - and R 1 are each independently an alkyl group. Each m1 independently represents an integer of 0 to 4. [6-2] X is a single bond, A is -(CH 2 ) p1 - and p1 is an integer from 1 to 10; R1 are each independently an alkyl group; Each m1 is independently an integer of 0 to 4; The film-forming material for lithography according to the above [6-1B]. [6-3] The film-forming material for lithography according to the above [6-2], wherein p1 is an integer of 1 to 6. [6-4] The film-forming material for lithography according to the above [6-2], wherein p1 is an integer of 1 to 3. [6-5] X's are each independently -CO- or -COO-; A is -(O(CH 2 ) q2 ) p3 - and q2 is an integer of 1 to 4, p3 is an integer from 1 to 20; R 1 are each independently an alkyl group; Each m1 is independently an integer of 0 to 4; The film-forming material for lithography according to the above [6-1B]. [6-6] -XAX- is -CO-(O(CH 2 ) q2 ) p3 The film-forming material for lithography according to the above [6-5], which is -COO-. Here, q2 is an integer from 1 to 4, and p3 is an integer from 1 to 20. [6-7] X is -O-, A is of the following structure:
[0030] [ka]
[0031] Y is -C(CH 3 ) 2 -or-C(CF 3 ) 2 - and R 1are each independently an alkyl group; Each m1 is independently an integer of 0 to 4; The film-forming material for lithography according to the above [6-1B]. [6-8] A has the structure:
[0032] [ka]
[0033] The film-forming material for lithography according to the above [6-7]. [6-9] R 1 each independently represents an alkyl group having 1 to 6 carbon atoms. [6-10] R 1 each independently represents an alkyl group having 1 to 3 carbon atoms. [7] The film-forming material for lithography according to [3] above, wherein the addition polymerization type itaconimide resin is represented by the following formula (2) or the following formula (3):
[0034] [ka]
[0035] (In formula (2), R 01 , R 02 , R 03 is defined as above, R 2 each independently represents a group having 0 to 10 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, m2 is independently an integer of 0 to 3, Each m2' is independently an integer of 0 to 4, n is an integer from 1 to 4.
[0036] [ka]
[0037] (In formula (3), R 01 , R 02 , R 03 is defined as above, R 3 and R 4 each independently represents a group having 0 to 10 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, m3 is independently an integer of 0 to 4, m4 is independently an integer of 0 to 4, n is an integer from 1 to 4. [7-1] R 2 , or R 3 and R 4 is an alkyl group. [7-2] The film-forming material for lithography according to any one of the above [4] to [7-1], wherein the heteroatom is selected from the group consisting of oxygen, fluorine, and silicon. [7-3] The film-forming material for lithography according to any one of the above [4] to [7-2], wherein the heteroatom is oxygen. [8] The film-forming material for lithography according to any one of the above [1] to [7-3], further comprising a crosslinking agent. [9] The film-forming material for lithography according to the above item [8], wherein the crosslinking agent is at least one selected from the group consisting of a phenol compound, an epoxy compound, a cyanate compound, an amino compound, a benzoxazine compound, a melamine compound, a guanamine compound, a glycoluril compound, a urea compound, an isocyanate compound, and an azide compound.
[10] The film-forming material for lithography according to [8] or [9] above, wherein the crosslinking agent has at least one allyl group.
[11] The film-forming material for lithography according to any one of [8] to
[10] above, wherein the content of the crosslinking agent is 0.1 to 100 parts by mass, relative to 100 parts by mass of the total amount of the compound having a group of formula (0).
[12] The film-forming material for lithography according to any one of the above [1] to
[11] , further comprising a crosslinking accelerator.
[13] The film-forming material for lithography according to the above
[12] , wherein the crosslinking accelerator is at least one selected from the group consisting of amines, imidazoles, organic phosphines, and Lewis acids.
[14] The film-forming material for lithography according to the above
[12] or
[13] , wherein the content of the crosslinking accelerator is 0.1 to 5 parts by mass, relative to 100 parts by mass of the total amount of the compound having a group of the formula (0).
[15] The film-forming material for lithography according to any one of the above [1] to
[14] , further comprising a radical polymerization initiator.
[16] The film-forming material for lithography according to the above
[15] , wherein the radical polymerization initiator is at least one selected from the group consisting of a ketone-based photopolymerization initiator, an organic peroxide-based polymerization initiator, and an azo-based polymerization initiator.
[17] The film-forming material for lithography according to the above
[15] or
[16] , wherein the content of the radical polymerization initiator is 0.05 to 25 parts by mass, relative to 100 parts by mass of the total amount of the compound having a group of the formula (0).
[18] A film-forming composition for lithography, comprising the film-forming material for lithography according to any one of the above [1] to
[17] and a solvent.
[19] The film-forming composition for lithography according to the above
[18] , further comprising an acid generator.
[20] The composition for forming a film for lithography according to the above
[18] or
[19] , wherein the film for lithography is an underlayer film for lithography. [twenty one] An underlayer film for lithography formed using the composition for forming a film for lithography according to item
[20] above. [twenty two] A step of forming an underlayer film on a substrate using the composition for forming a film for lithography according to the above item
[20] . forming at least one photoresist layer on the underlayer film; and exposing predetermined areas of the photoresist layer to radiation and developing; A method for forming a resist pattern comprising the steps of: [twenty three] forming an underlayer film on a substrate using the film-forming composition for lithography described in
[20] above; forming an intermediate layer film on the underlayer film using a resist intermediate layer film material containing silicon atoms; forming at least one photoresist layer on the intermediate layer film; A step of exposing predetermined areas of the photoresist layer to radiation and developing the layer to form a resist pattern. a step of etching the intermediate layer film using the resist pattern as a mask; A step of etching the underlayer film using the obtained intermediate layer film pattern as an etching mask. a step of forming a pattern on the substrate by etching the substrate using the obtained underlayer film pattern as an etching mask; A pattern forming method comprising: [twenty four] A step of dissolving the film-forming material for lithography according to any one of the above [1] to
[17] in a solvent to obtain an organic phase; a first extraction step of contacting the organic phase with an acidic aqueous solution to extract impurities in the film-forming material for lithography; Including, The method for purification, wherein the solvent used in the step of obtaining the organic phase comprises a solvent that is optionally immiscible with water. [twenty five] The acidic aqueous solution is a mineral acid aqueous solution or an organic acid aqueous solution, The mineral acid aqueous solution contains one or more acids selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid, The purification method according to
[24] above, wherein the aqueous organic acid solution contains one or more acids selected from the group consisting of acetic acid, propionic acid, oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, tartaric acid, citric acid, methanesulfonic acid, phenolsulfonic acid, p-toluenesulfonic acid, and trifluoroacetic acid.
[26] The purification method according to
[24] or
[25] , wherein the water-immiscible solvent is one or more solvents selected from the group consisting of toluene, 2-heptanone, cyclohexanone, cyclopentanone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, and ethyl acetate.
[27] The purification method according to any one of
[24] to
[26] above, further comprising a second extraction step of contacting the organic phase with water after the first extraction step to extract impurities in the film-forming material for lithography.
[28] An addition polymerization type itaconimide resin represented by the following formula (2) or the following formula (3):
[0038] [ka]
[0039] (In formula (2), R 01 , R 02 , R 03 is defined as above, R 2 each independently represents a group having 0 to 10 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, m2 is independently an integer of 0 to 3, Each m2' is independently an integer of 0 to 4, n is an integer from 1 to 4.
[0040] [ka]
[0041] (In formula (3), R 01 , R 02 , R 03 is defined as above, R 3 and R 4 each independently represents a group having 0 to 10 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, m3 is independently an integer of 0 to 4, m4 is independently an integer of 0 to 4, n is an integer from 1 to 4.
[29] R 2 , or R 3 and R 4 is an alkyl group.
[30] The addition polymerization itaconimide resin according to
[28] or
[29] above, wherein the heteroatom is selected from the group consisting of oxygen, fluorine, and silicon.
[31] The addition-polymerizable itaconimide resin according to any one of the above
[28] to
[30] , wherein the heteroatom is oxygen. Effect of the Invention
[0042] According to the present invention, it is possible to provide a film-forming material for lithography, which is useful for forming a photoresist underlayer film to which a wet process can be applied and which has excellent etching resistance, a film-forming composition for lithography containing the material, and an underlayer film for lithography and a pattern formation method using the composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0043] Hereinafter, embodiments of the present invention will be described. The following embodiments are merely examples for explaining the present invention, and the present invention is not limited to these embodiments.
[0044] [Film-forming materials for lithography] The film-forming material for lithography is a material capable of forming a film for lithography, which contains a compound having a group of the following formula (0) or a cured product thereof. In one embodiment, the film-forming material for lithography is a composition consisting of only the compound, and in another embodiment, which contains the compound and other components excluding the solvent. The film-forming material for lithography of the present invention is particularly useful for a photoresist underlayer film having excellent heat resistance, etching resistance, embedding properties into uneven substrates, and film flatness. A material that contains the film-forming material for lithography and a solvent and can be used to form a film is called a "film-forming composition for lithography."
[0045] A film-forming material for lithography, which is one embodiment of the present invention, contains a compound having a group of the following formula (0) (hereinafter, also referred to as an "itaconimide compound" in the present invention).
[0046] [ka]
[0047] The itaconimide compound can be obtained, for example, by a dehydration ring-closing reaction between a compound having one or more primary amino groups in the molecule and itaconic anhydride. Examples of the itaconimide compound include a polyitaconimide compound and an itaconimide resin. The polyitaconimide compound is a compound having a plurality of groups represented by formula (0). In one embodiment, the polyitaconimide compound is crystalline. The itaconimide resin is a mixture of a plurality of itaconimide compounds having different molecular weights. In one embodiment, the itaconimide resin is amorphous.
[0048] In formula (0), R 01 , R 02 , R 03 are each independently a hydrogen atom, a linear or branched alkyl group having 1 to 18 carbon atoms, a cyclic alkyl group having 3 to 18 carbon atoms, an aryl group having 6 to 18 carbon atoms, an aralkyl group having 7 to 30 carbon atoms, or an alkylaryl group having 7 to 30 carbon atoms. From the viewpoint of the reactivity of the carbon-carbon double bond, R 01is preferably a hydrogen atom or a methyl group, more preferably a hydrogen atom. 02 is preferably a hydrogen atom or a methyl group, more preferably a hydrogen atom. From the viewpoint of availability of raw materials, R 03 is preferably a hydrogen atom or a linear or branched alkyl group having 1 to 18 carbon atoms, and more preferably a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms.
[0049] The content of the itaconimide compound in the matrix-forming component in the film-forming material for lithography of this embodiment is preferably 0.1 to 100% by mass, more preferably 0.5 to 100% by mass, and even more preferably 1 to 100% by mass. From the viewpoint of heat resistance and etching resistance, the content is preferably 51 to 100% by mass, more preferably 60 to 100% by mass, even more preferably 70 to 100% by mass, and particularly preferably 80 to 100% by mass. Other matrix-forming components include highly heat-resistant polymers and the like.
[0050] The itaconimide compound of the present embodiment can be used in combination with a conventional underlayer film-forming composition to improve the heat resistance of the conventional underlayer film-forming composition. In this case, the content of the itaconimide compound in the components excluding the solvent in the mixture obtained by the combination is preferably 1 to 50 mass%, more preferably 1 to 30 mass%. Examples of conventional underlayer film-forming compositions include, but are not limited to, those described in International Publication No. 2013 / 024779.
[0051] The itaconimide compound in the film-forming material for lithography of this embodiment is characterized in that it has a function other than that of an acid generator or a basic compound for forming a film for lithography.
[0052] As the polyitaconimide compound and itaconimide resin used in the film-forming material for lithography of this embodiment, from the viewpoints of raw material availability and production suited to mass production, a bisitaconimide compound and an addition polymerization type itaconimide resin are preferred.
[0053] <Bisitaconimide compounds> The bisitaconimide compound is preferably represented by the following formula (1).
[0054] [ka]
[0055] In formula (1), R 01 , R 02 , R 03 is as described above. Z is a single bond or a divalent group having 0 to 100 carbon atoms which may contain a heteroatom. Z may be a divalent hydrocarbon group having 1 to 100 carbon atoms which may contain a heteroatom. The number of carbon atoms in the hydrocarbon group may be 1 to 80, 1 to 60, 1 to 40, or 1 to 20, etc. The hydrocarbon is linear, branched, or cyclic. Examples of heteroatoms include oxygen, nitrogen, sulfur, fluorine, and silicon.
[0056] The bisitaconimide compound is more preferably represented by the following formula (1A).
[0057] [ka]
[0058] In the formula (1A), from the viewpoint of improving heat resistance and etching resistance, X is independently a single bond, -O-, -CH 2 -, -C(CH 3 ) 2 -, -CO-, -C(CF 3 ) 2 From the viewpoint of heat resistance, X is preferably a single bond, and from the viewpoint of solubility, X is preferably -COO-.
[0059] A is a single bond, an oxygen atom, or a divalent hydrocarbon group having 1 to 80 carbon atoms which may contain a heteroatom (for example, oxygen, nitrogen, sulfur, or fluorine). From the viewpoint of improving heat resistance and etching resistance, A is a single bond, an oxygen atom, -(CH 2 ) n -, -CH 2 C(CH 3 ) 2 CH 2 -, -(C(CH 3 ) 2 ) p -, -(O(CH 2 ) q ) p -, -(O(C 6 H 4 )) p - or any of the following structures: where p is an integer of 1 to 20, and from the viewpoint of improving heat resistance, is more preferably an integer of 1 to 2. q is an integer of 1 to 4, and preferably an integer of 2 to 4.
[0060] [ka]
[0061] Y is a single bond, -O-, -CH 2 -, -C(CH 3 ) 2 -, -C(CF 3 ) 2 - or any of the following groups:
[0062] [ka]
[0063] From the viewpoint of improving heat resistance, Y is preferably a single bond.
[0064] R 1R are each independently a group having 0 to 30 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom (e.g., oxygen, nitrogen, sulfur, fluorine, chlorine, bromine, iodine). 1 is preferably a group having 0 to 20 or 0 to 10 carbon atoms which may contain a heteroatom (e.g., oxygen, nitrogen, sulfur, fluorine, chlorine, bromine, iodine). From the viewpoint of improving solubility in organic solvents, R 1 is preferably a hydrocarbon group. For example, R 1 Examples of the alkyl group include an alkyl group (for example, an alkyl group having 1 to 6 or 1 to 3 carbon atoms), and specific examples thereof include a methyl group, an ethyl group, and the like.
[0065] Each m1 is independently an integer of 0 to 4. m1 is preferably an integer of 0 to 2, and more preferably 1 or 2 from the viewpoints of raw material availability and improving solubility.
[0066] One embodiment of the compound represented by formula (1A) is Each X is independently a single bond, -O-, -CO-, or -COO-; A is a single bond, an oxygen atom, -(CH 2 ) p1 -, -CH 2 C(CH 3 ) 2 CH 2 -, -(O(CH 2 ) q2 ) p3 or the structure
[0067] [ka]
[0068] p1 is an integer from 1 to 10; q2 is an integer from 1 to 4; p3 is an integer from 1 to 20; Y is -C(CH 3 ) 2 -or-C(CF 3 ) 2 - and R1 each independently represents an alkyl group (e.g., an alkyl group having 1 to 6 or 1 to 3 carbon atoms), Each m1 independently represents an integer of 0 to 4.
[0069] One embodiment of the compound represented by formula (1A) is X is a single bond, A is -(CH 2 ) p1 - and p1 is an integer from 1 to 10; R 1 each independently represents an alkyl group (e.g., an alkyl group having 1 to 6 or 1 to 3 carbon atoms), Each m1 independently represents an integer of 0 to 4. In particular, p1 is preferably 1 to 6 or 1 to 3.
[0070] One embodiment of the compound represented by formula (1A) is Each X is independently -CO- or -COO-; A is -(O(CH 2 ) q2 ) p3 - and q2 is an integer from 1 to 4; p3 is an integer from 1 to 20; R 1 each independently represents an alkyl group (e.g., an alkyl group having 1 to 6 or 1 to 3 carbon atoms), Each m1 independently represents an integer of 0 to 4. In particular, -XAX- is -CO-(O(CH 2 ) q2 ) p3 -COO- is preferred.
[0071] One embodiment of the compound represented by formula (1A) is X is -O-, A is of the following structure:
[0072] [ka]
[0073] Y is -C(CH 3 ) 2 -or-C(CF 3 ) 2 - and R 1 each independently represents an alkyl group (e.g., an alkyl group having 1 to 6 or 1 to 3 carbon atoms), Each m1 independently represents an integer of 0 to 4. In particular, A preferably has the following structure:
[0074] [ka]
[0075] <Addition polymerization type itaconimide resin> The addition polymerization type itaconimide resin is preferably a resin represented by the following formula (2) or (3) from the viewpoint of improving etching resistance.
[0076] [ka]
[0077] In the formula (2), R 01 , R 02 , R 03 is as mentioned above. R 2 are each independently a group having 0 to 10 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom (e.g., oxygen, nitrogen, sulfur, fluorine, chlorine, bromine, iodine). 2 is preferably a hydrocarbon group from the viewpoint of improving solubility in an organic solvent. For example, R 2 Examples of the alkyl group include an alkyl group (for example, an alkyl group having 1 to 6 or 1 to 3 carbon atoms), and specific examples thereof include a methyl group, an ethyl group, and the like.
[0078] Each m2 is independently an integer of 0 to 3. Moreover, m2 is preferably 0 or 1, and more preferably 0 from the viewpoint of availability of raw materials. Each m2' is independently an integer of 0 to 4. Moreover, m2' is preferably 0 or 1, and more preferably 0 from the viewpoint of availability of raw materials. n is an integer of 0 to 4. Furthermore, n is preferably an integer of 1 to 4 or 0 to 2, and more preferably an integer of 1 or 2 from the viewpoint of improving heat resistance. As described above, a resin is a mixture of compounds having different molecular weights, so for example, a compound in which n is represented by an integer (such as a pure product in which n=1) is a polyitaconimide compound. [ka]
[0079] In the above formula (3), R 01 , R 02 , R 03 is as mentioned above. R 3 and R 4 are each independently a group having 0 to 10 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom (e.g., oxygen, nitrogen, sulfur, fluorine, chlorine, bromine, iodine). 3 and R 4 is preferably a hydrocarbon group from the viewpoint of improving solubility in an organic solvent. For example, R 3 and R 4 Examples of the alkyl group include an alkyl group (for example, an alkyl group having 1 to 6 or 1 to 3 carbon atoms), and specific examples thereof include a methyl group, an ethyl group, and the like. Each m3 is independently an integer of 0 to 4. Moreover, m3 is preferably an integer of 0 to 2, and more preferably 0 from the viewpoint of availability of raw materials. Each m4 is independently an integer of 0 to 4. Moreover, m4 is preferably an integer of 0 to 2, and more preferably 0 from the viewpoint of availability of raw materials. n is an integer of 0 to 4. Furthermore, n is preferably an integer of 1 to 4 or 0 to 2, and more preferably an integer of 1 or 2 from the viewpoint of availability of raw materials.
[0080] The lithography film-forming material of this embodiment can be applied to a wet process. In addition, the lithography film-forming material of this embodiment has an aromatic structure and a rigid itaconimide skeleton, and even when used alone, the itaconimide group undergoes a crosslinking reaction by high-temperature baking, thereby exhibiting high heat resistance. As a result, deterioration of the film during high-temperature baking is suppressed, and an underlayer film having excellent etching resistance against oxygen plasma etching and the like can be formed. Furthermore, despite having an aromatic structure, the lithography film-forming material of this embodiment has high solubility in organic solvents and high solubility in safe solvents. Furthermore, the lithography underlayer film made of the lithography film-forming composition of this embodiment described later has excellent embedding properties in step substrates and film flatness, and not only has good stability of product quality, but also has excellent adhesion to resist layers and resist intermediate layer film materials, so that an excellent resist pattern can be obtained.
[0081] Specific examples of the bisitaconimide compound used in the present embodiment include phenylene skeleton-containing bisitaconimides such as m-phenylene bisitaconimide, 4-methyl-1,3-phenylene bisitaconimide, 4,4-diphenylmethane bisitaconimide, 4,4'-diphenylsulfone bisitaconimide, 1,3-bis(3-itaconimide phenoxy)benzene, 1,3-bis(4-itaconimide phenoxy)benzene, 1,4-bis(3-itaconimide phenoxy)benzene, and 1,4-bis(4-itaconimide phenoxy)benzene; bis (3-ethyl-5-methyl-4-itaconimidophenyl)methane, 1,1-bis(3-ethyl-5-methyl-4-itaconimidophenyl)ethane, 2,2-bis(3-ethyl-5-methyl-4-itaconimidophenyl)propane, N,N'-4,4'-[3,3'-dimethyl-diphenylmethane]bisitaconimide, N,N'-4,4'-[3,3'-dimethyl-1,1-diphenylethane]bisitaconimide, N,N'-4,4'-[3,3'-dimethyl-1,1-diphenylpropane]bisitaconimide, N,N'-4,4'-[3,3 diphenylalkane skeleton-containing bisitaconimides such as N,N'-4,4'-[3,3'-diethyl-diphenylmethane]bisitaconimide, N,N'-4,4'-[3,3'-dipropyl-diphenylmethane]bisitaconimide, and N,N'-4,4'-[3,3'-dibutyl-diphenylmethane]bisitaconimide; biphenyl skeleton-containing bisitaconimides such as N,N'-4,4'-[3,3'-dimethyl-biphenylene]bisitaconimide and N,N'-4,4'-[3,3'-diethyl-biphenylene]bisitaconimide; 1,6-hexanebisitaconimide; Aliphatic skeleton bisitaconimides such as 1,6-bisitaconimide(2,2,4-trimethyl)hexane, 1,3-dimethylenecyclohexane bisitaconimide, and 1,4-dimethylenecyclohexane bisitaconimide, as well as 1,3-bis(3-aminopropyl)-1,1,2,2-tetramethyldisiloxane, 1,3-bis(3-aminobutyl)-1,1,2,2-tetramethyldisiloxane, bis(4-aminophenoxy)dimethylsilane, 1,3-bis(4-aminophenoxy)tetramethyldisiloxane, and 1,1,3,3-tetramethyl-1,3-bis(4-aminophenyl)disiloxane, 1,1,3,3-tetraphenoxy-1,3-bis(2-aminoethyl)disiloxane, 1,1,3,3-tetraphenyl-1,3-bis(2-aminoethyl)disiloxane, 1,1,3,3-tetraphenyl-1,3-bis(3-aminopropyl)disiloxane, 1,1,3,3-tetramethyl-1,3-bis(2-aminoethyl)disiloxane, 1,1,3,3-tetramethyl-1,3-bis(3 -aminopropyl)disiloxane, 1,1,3,3-tetramethyl-1,3-bis(4-aminobutyl)disiloxane, 1,3-dimethyl-1,3-dimethoxy-1,3-bis(4-aminobutyl)disiloxane, 1,1,3,3,5,5-hexamethyl-1,5-bis(4-aminophenyl)trisiloxane, 1,1,5,5-tetraphenyl-3,3-dimethyl-1,5-bis(3-aminopropyl)trisiloxane, 1,1,5,5-tetraf 1,1,5,5-tetraphenyl-3,3-dimethoxy-1,5-bis(4-aminobutyl)trisiloxane, 1,1,5,5-tetraphenyl-3,3-dimethoxy-1,5-bis(5-aminopentyl)trisiloxane, 1,1,5,5-tetramethyl-3,3-dimethoxy-1,5-bis(2-aminoethyl)trisiloxane, 1,1,5,5-tetramethyl-3,3-dimethoxy-1,5-bis(4-aminobutyl)trisiloxane, 1,1,5,5-tetramethyl- Examples of the bisitaconimide compound include diaminosiloxanes such as 3,3-dimethoxy-1,5-bis(5-aminopentyl)trisiloxane, 1,1,3,3,5,5-hexamethyl-1,5-bis(3-aminopropyl)trisiloxane, 1,1,3,3,5,5-hexaethyl-1,5-bis(3-aminopropyl)trisiloxane, and 1,1,3,3,5,5-hexapropyl-1,5-bis(3-aminopropyl)trisiloxane.
[0082] Among the bisitaconimide compounds, bis(3-ethyl-5-methyl-4-itaconimidophenyl)methane, N,N'-4,4'-[3,3'-dimethyl-diphenylmethane]bisitaconimide, and N,N'-4,4'-[3,3'-diethyldiphenylmethane]bisitaconimide are particularly preferred because of their excellent solvent solubility and heat resistance.
[0083] Of the bisitaconimide compounds and addition polymerization type itaconimide resins used in this embodiment, addition polymerization type itaconimide resins are more preferred from the viewpoints of heat resistance of the lithography film, adhesion to the resist intermediate layer, and resistance to film defects.
[0084] <Crosslinking agent> The film-forming material for lithography of the present embodiment may contain, in addition to the bisitaconimide compound or the addition polymerization type itaconimide resin, a crosslinking agent as necessary from the viewpoint of lowering the curing temperature and suppressing intermixing.
[0085] The crosslinking agent is not particularly limited as long as it crosslinks with itaconimide, and any known crosslinking system can be applied. Specific examples of crosslinking agents that can be used in this embodiment include, but are not limited to, phenol compounds, epoxy compounds, cyanate compounds, amino compounds, benzoxazine compounds, acrylate compounds, melamine compounds, guanamine compounds, glycoluril compounds, urea compounds, isocyanate compounds, and azide compounds. These crosslinking agents can be used alone or in combination of two or more. Among these, benzoxazine compounds, epoxy compounds, or cyanate compounds are preferred, and benzoxazine compounds are more preferred from the viewpoint of improving etching resistance.
[0086] In the crosslinking reaction between itaconimide and a crosslinking agent, for example, an active group (a phenolic hydroxyl group, an epoxy group, a cyanate group, an amino group, or a phenolic hydroxyl group formed by ring-opening of an alicyclic portion of benzoxazine) of the crosslinking agent undergoes an addition reaction with a carbon-carbon double bond constituting the itaconimide group to form a crosslink, and in addition, two carbon-carbon double bonds of the bisitaconimide compound of this embodiment undergo polymerization to form a crosslink.
[0087] As the phenol compound, known compounds can be used. For example, compounds described in International Publication No. 2018-016614 can be used. In terms of heat resistance and solubility, aralkyl phenol resins are preferable.
[0088] As the epoxy compound, known compounds can be used, and are selected from those having two or more epoxy groups in one molecule. For example, those described in International Publication No. 2018-016614 can be mentioned. These epoxy resins may be used alone or in combination of two or more. From the viewpoint of heat resistance and solubility, epoxy resins that are solid at room temperature, such as epoxy resins obtained from phenol aralkyl resins and biphenyl aralkyl resins, are preferable.
[0089] The cyanate compound is not particularly limited as long as it is a compound having two or more cyanate groups in one molecule, and known compounds can be used. For example, those described in International Publication No. 2011 / 108524 can be mentioned. In this embodiment, preferred cyanate compounds include those having a structure in which a hydroxyl group of a compound having two or more hydroxyl groups in one molecule is substituted with a cyanate group. In addition, the cyanate compound is preferably one having an aromatic group, and a structure in which a cyanate group is directly bonded to an aromatic group can be suitably used. Examples of such cyanate compounds include those described in International Publication No. 2018 / 016614. These cyanate compounds may be used alone or in appropriate combination of two or more. In addition, the above-mentioned cyanate compounds may be in the form of any of a monomer, an oligomer, and a resin.
[0090] Examples of the amino compound include those described in WO 2018 / 016614.
[0091] The oxazine structure of the benzoxazine compound is not particularly limited, and examples thereof include oxazine structures having an aromatic group including a condensed polycyclic aromatic group, such as benzoxazine and naphthoxazine.
[0092] Examples of benzoxazine compounds include compounds represented by the following general formulas (a) to (f): In the following general formulas, a bond extending from a group to the center of a ring indicates that the group is bonded to any of the carbons constituting the ring to which a substituent can be bonded.
[0093] [ka]
[0094] In general formulas (a) to (c), R 1 and R 2 Each independently represents an organic group having 1 to 30 carbon atoms. 3 ~R 6 each independently represents hydrogen or a hydrocarbon group having 1 to 6 carbon atoms. In addition, in the general formulae (c), (d) and (f), each X independently represents a single bond, -O-, -S-, -SS-, -SO 2 -, -CO-, -CONH-, -NHCO-, -C(CH 3 ) 2 -, -C(CF 3 ) 2 -, -(CH 2 )m-, -O-(CH 2 )mO-, -S-(CH 2 )mS-, where m is an integer of 1 to 6. In addition, in the general formulae (e) and (f), Y independently represents a single bond, -O-, -S-, -CO-, -C(CH 3 ) 2 -, -C(CF 3 ) 2 - or alkylene having 1 to 3 carbon atoms.
[0095] The benzoxazine compound also includes an oligomer or polymer having an oxazine structure in the side chain, and an oligomer or polymer having a benzoxazine structure in the main chain.
[0096] The benzoxazine compound can be produced by a method similar to that described in WO 2004 / 009708, JP-A 11-12258, and JP-A 2004-352670.
[0097] Specific examples of the melamine compound include those described in International Publication No. 2018 / 016614.
[0098] Specific examples of the guanamine compound include those described in WO 2018 / 016614.
[0099] Specific examples of the glycoluril compound include those described in WO 2018 / 016614.
[0100] Specific examples of the urea compound include those described in WO 2018 / 016614.
[0101] In addition, in this embodiment, from the viewpoint of improving crosslinking, a crosslinking agent having at least one allyl group may be used. Specific examples of crosslinking agents having at least one allyl group include, but are not limited to, those described in International Publication No. 2018 / 016614. These may be used alone or in a mixture of two or more kinds. Among these, from the viewpoint of excellent compatibility with bisitaconimide compounds or addition polymerization type itaconimide resins, allylphenols such as 2,2-bis(3-allyl-4-hydroxyphenyl)propane, 1,1,1,3,3,3-hexafluoro-2,2-bis(3-allyl-4-hydroxyphenyl)propane, bis(3-allyl-4-hydroxyphenyl)sulfone, bis(3-allyl-4-hydroxyphenyl)sulfide, and bis(3-allyl-4-hydroxyphenyl)ether are preferred.
[0102] The lithography film-forming material of the present embodiment can be formed by crosslinking and curing the bisitaconimide compound or the addition polymerization type itaconimide resin alone or in combination with the crosslinking agent by a known method. Examples of the crosslinking method include heat curing and photocuring.
[0103] The content of the components such as the crosslinking agent is determined based on 100 parts by mass of the total amount of the itaconimide compound. In this embodiment, since it is preferable to use a bisitaconimide compound or an addition polymerization type itaconimide resin as the itaconimide compound, the content of the components such as the crosslinking agent will be described below based on 100 parts by mass of the total amount of the bisitaconimide compound and the addition polymerization type itaconimide resin.
[0104] The content of the crosslinking agent is usually in the range of 0.1 to 10,000 parts by mass, preferably in the range of 0.1 to 10000 parts by mass from the viewpoints of heat resistance and solubility, more preferably in the range of 0.1 to 100 parts by mass, even more preferably in the range of 1 to 50 parts by mass, and most preferably in the range of 1 to 30 parts by mass, relative to 100 parts by mass of the itaconimide compound (preferably the total mass of the bisitaconimide compound and the addition polymerization type itaconimide resin).
[0105] In the film-forming material for lithography of this embodiment, a crosslinking accelerator for accelerating the crosslinking and curing reaction can be used as necessary.
[0106] The crosslinking accelerator is not particularly limited as long as it accelerates crosslinking and curing reaction, and examples thereof include amines, imidazoles, organic phosphines, Lewis acids, etc. These crosslinking accelerators can be used alone or in combination of two or more. Among these, imidazoles or organic phosphines are preferred, and imidazoles are more preferred from the viewpoint of lowering the crosslinking temperature.
[0107] The crosslinking accelerator is not limited to the following, but examples thereof include those described in International Publication No. 2018 / 016614. The amount of the crosslinking accelerator is usually preferably in the range of 0.1 to 10 parts by mass, more preferably in the range of 0.1 to 5 parts by mass, and even more preferably in the range of 0.1 to 3 parts by mass, when the total mass of the bisitaconimide compound and the addition polymerization type itaconimide resin is 100 parts by mass, from the viewpoints of ease of control and economic efficiency.
[0108] <Radical polymerization initiator> The film-forming material for lithography of the present embodiment may contain a radical polymerization initiator as necessary. The radical polymerization initiator may be a photopolymerization initiator that initiates radical polymerization by light, or a thermal polymerization initiator that initiates radical polymerization by heat.
[0109] Such radical polymerization initiators are not particularly limited, and conventionally used ones can be appropriately adopted. For example, those described in International Publication No. 2018 / 016614 can be mentioned. As the radical polymerization initiator in this embodiment, one of these may be used alone or two or more may be used in combination, and other known polymerization initiators may be further combined.
[0110] The content of the radical polymerization initiator may be an amount stoichiometrically required for the itaconimide compound (preferably the total mass of the bisitaconimide compound and the addition polymerization type itaconimide resin), but when the total mass of the bisitaconimide compound and the addition polymerization type itaconimide resin is taken as 100 parts by mass, it is preferably 0.05 to 25 parts by mass, and more preferably 0.1 to 10 parts by mass. When the content of the radical polymerization initiator is 0.05 parts by mass or more, it tends to be possible to prevent the curing of the bisitaconimide compound or the itaconimide resin from becoming insufficient, while when the content of the radical polymerization initiator is 25 parts by mass or less, it tends to be possible to prevent the long-term storage stability of the film-forming material for lithography at room temperature from being impaired.
[0111] [Method for purifying film-forming materials for lithography] The lithographic film-forming material can be purified by washing with an acidic aqueous solution. The purification method includes a step of dissolving the lithographic film-forming material in an organic solvent that is not miscible with water to obtain an organic phase, contacting the organic phase with an acidic aqueous solution to perform an extraction treatment (first extraction step), thereby transferring the metal content contained in the organic phase containing the lithographic film-forming material and the organic solvent to the aqueous phase, and then separating the organic phase from the aqueous phase. The purification can significantly reduce the content of various metals in the lithographic film-forming material of the present invention.
[0112] The organic solvent that is not miscible with water is not particularly limited, but is preferably an organic solvent that can be safely used in the semiconductor manufacturing process. The amount of the organic solvent used is usually about 1 to 100 times by mass relative to the compound used.
[0113] Specific examples of the organic solvent to be used include those described in International Publication No. 2015 / 080240. Among these, toluene, 2-heptanone, cyclohexanone, cyclopentanone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, ethyl acetate, etc. are preferred, and cyclohexanone and propylene glycol monomethyl ether acetate are particularly preferred. These organic solvents can be used alone or in combination of two or more.
[0114] The acidic aqueous solution is appropriately selected from among aqueous solutions in which a generally known organic or inorganic compound is dissolved in water. For example, those described in International Publication No. 2015 / 080240 can be mentioned. These acidic aqueous solutions can be used alone or in combination of two or more. Examples of the acidic aqueous solution include mineral acid aqueous solutions and organic acid aqueous solutions. Examples of the mineral acid aqueous solution include an aqueous solution containing one or more selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid. Examples of the organic acid aqueous solution include an aqueous solution containing one or more selected from the group consisting of acetic acid, propionic acid, oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, tartaric acid, citric acid, methanesulfonic acid, phenolsulfonic acid, p-toluenesulfonic acid, and trifluoroacetic acid. In addition, as the acidic aqueous solution, an aqueous solution of sulfuric acid, nitric acid, and a carboxylic acid such as acetic acid, oxalic acid, tartaric acid, or citric acid is preferable, and an aqueous solution of sulfuric acid, oxalic acid, tartaric acid, or citric acid is more preferable, and an aqueous solution of oxalic acid is particularly preferable. It is considered that polycarboxylic acids such as oxalic acid, tartaric acid, and citric acid coordinate with metal ions and generate a chelating effect, so that more metals can be removed. In addition, the water used here is preferably one with a low metal content, such as ion-exchanged water, in line with the object of the present invention.
[0115] The pH of the acidic aqueous solution is not particularly limited, but if the acidity of the aqueous solution is too high, it may adversely affect the compound or resin used, which is not preferable. The pH range is usually about 0 to 5, and more preferably about pH 0 to 3.
[0116] The amount of the acidic aqueous solution used is not particularly limited, but if the amount is too small, it is necessary to perform extraction many times to remove metals, and conversely, if the amount of the aqueous solution is too large, the total amount of liquid becomes large, which may cause operational problems. The amount of the aqueous solution used is usually 10 to 200 parts by mass, preferably 20 to 100 parts by mass, based on the solution of the film-forming material for lithography.
[0117] The metal components can be extracted by contacting the acidic aqueous solution with a solution (B) containing a film-forming material for lithography and an organic solvent that is arbitrarily immiscible with water.
[0118] The temperature during the extraction treatment is usually 20 to 90°C, preferably in the range of 30 to 80°C. The extraction operation is carried out, for example, by mixing thoroughly by stirring or the like, and then allowing to stand. As a result, metals contained in the solution containing the compound to be used and the organic solvent are transferred to the aqueous phase. This operation also reduces the acidity of the solution, making it possible to suppress deterioration of the compound to be used.
[0119] After the extraction treatment, the organic phase containing the compound and the organic solvent to be used is separated from the aqueous phase, and the solution containing the organic solvent is recovered by decantation or the like. The time for standing is not particularly limited, but if the time for standing is too short, the separation of the organic phase containing the organic solvent and the aqueous phase becomes poor, which is not preferable. Usually, the time for standing is 1 minute or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more. In addition, the extraction treatment may be performed only once, but it is also effective to repeat the operations of mixing, standing, and separation several times.
[0120] When such an extraction treatment is carried out using an acidic aqueous solution, it is preferable to subject the organic phase containing the organic solvent extracted and recovered from the aqueous solution after the treatment to an extraction treatment with water (second extraction step). The extraction operation is carried out by mixing thoroughly by stirring or the like and then leaving it to stand. The resulting solution is separated into an organic phase containing the compound and the organic solvent and an aqueous phase, and the organic phase is recovered by decantation or the like. In addition, the water used here is preferably one with a low metal content, such as ion-exchanged water, in line with the object of the present invention. The extraction treatment may be carried out only once, but it is also effective to repeat the operations of mixing, leaving to stand, and separating several times. In addition, the ratio of both used in the extraction treatment, and the conditions such as temperature and time are not particularly limited, but may be the same as in the case of the contact treatment with the acidic aqueous solution.
[0121] Water mixed in the thus obtained solution containing the film-forming material for lithography and the organic solvent can be easily removed by performing an operation such as vacuum distillation. In addition, the concentration of the compound can be adjusted to any desired concentration by adding an organic solvent as necessary.
[0122] The method of obtaining only the film-forming material for lithography from the obtained solution containing the organic solvent can be carried out by a known method such as vacuum removal, separation by reprecipitation, or a combination thereof. If necessary, known treatments such as concentration, filtration, centrifugation, drying, etc. The above purification method is preferably carried out when the film-forming material for lithography is a compound having a group of formula (0) (itaconimide compound).
[0123] [Film-forming composition for lithography] The composition for forming a film for lithography according to the present embodiment contains the film-forming material for lithography and a solvent. The film for lithography is, for example, an underlayer film for lithography.
[0124] The lithography film-forming composition of the present embodiment can be applied to a substrate, and then heated as necessary to evaporate the solvent, followed by heating or light irradiation to form a desired cured film. The lithography film-forming composition of the present embodiment can be applied by any method, and for example, methods such as spin coating, dip coating, flow coating, inkjet coating, spraying, bar coating, gravure coating, slit coating, roll coating, transfer printing, brush coating, blade coating, and air knife coating can be appropriately adopted.
[0125] The heating temperature of the film is not particularly limited for the purpose of evaporating the solvent, and can be, for example, 40 to 400°C. The heating method is not particularly limited, and for example, evaporation can be performed using a hot plate or oven under an appropriate atmosphere such as air, an inert gas such as nitrogen, or in a vacuum. The heating temperature and heating time can be selected according to the processing step of the target electronic device, and heating conditions can be selected such that the physical properties of the obtained film are compatible with the required characteristics of the electronic device. The conditions for light irradiation are also not particularly limited, and appropriate irradiation energy and irradiation time can be adopted depending on the film-forming material for lithography used.
[0126] <Solvent> The solvent used in the film-forming composition for lithography of the present embodiment is not particularly limited as long as it at least dissolves the itaconimide compound, preferably a bisitaconimide or an addition polymerization type itaconimide resin, and any known solvent can be used as appropriate.
[0127] Specific examples of the solvent include those described in International Publication No. 2013 / 024779. These solvents may be used alone or in combination of two or more.
[0128] Among the above solvents, cyclohexanone, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, ethyl lactate, methyl hydroxyisobutyrate, and anisole are particularly preferred from the viewpoint of safety.
[0129] The content of the solvent is not particularly limited, but from the viewpoints of solubility and film formation, the content is preferably 25 to 9,900 parts by mass, more preferably 400 to 7,900 parts by mass, and even more preferably 900 to 4,900 parts by mass, relative to 100 parts by mass of the total mass of the itaconimide compound in the film-forming material for lithography (preferably the total mass of the bisitaconimide compound and the addition polymerization type itaconimide resin).
[0130] <Acid generator> The film-forming composition for lithography of the present embodiment may contain an acid generator as necessary from the viewpoint of further promoting the crosslinking reaction, etc. As the acid generator, there are known ones that generate an acid by thermal decomposition, ones that generate an acid by light irradiation, etc., and any of them can be used.
[0131] Examples of the acid generator include those described in WO2013 / 024779. Among these, particularly preferred are di-tert-butyldiphenyliodonium nonafluoromethanesulfonate, diphenyliodonium trifluoromethanesulfonate, (p-tert-butoxyphenyl)phenyliodonium trifluoromethanesulfonate, diphenyliodonium p-toluenesulfonate, (p-tert-butoxyphenyl)phenyliodonium p-toluenesulfonate, triphenylsulfonium trifluoromethanesulfonate, (p-tert-butoxyphenyl)diphenylsulfonium trifluoromethanesulfonate, tris(p-tert-butoxyphenyl)sulfonium trifluoromethanesulfonate, triphenylsulfonium p-toluenesulfonate, (p-tert-butoxyphenyl)diphenylsulfonium p-toluenesulfonate, tris(p-tert-butoxyphenyl)sulfonium p-toluenesulfonate, trinaphthylsulfonium trifluoromethanesulfonate, trifluoromethanesulfonate, onium salts such as cyclohexylmethyl(2-oxocyclohexyl)sulfonium trifluoride, (2-norbornyl)methyl(2-oxocyclohexyl)sulfonium trifluoride, and 1,2'-naphthylcarbonylmethyltetrahydrothiophenium triflate; bis(benzenesulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, bis(cyclohexylsulfonyl)diazomethane, bis(n-butylsulfonyl)diazomethane, bis(isopropyl)sulfonate ... diazomethane derivatives such as bis-(p-toluenesulfonyl)-α-dimethylglyoxime, bis-(n-butanesulfonyl)-α-dimethylglyoxime, and bissulfone derivatives such as bisnaphthylsulfonylmethane;Sulfonate derivatives of N-hydroxyimide compounds such as N-hydroxysuccinimide methanesulfonate, N-hydroxysuccinimide trifluoromethanesulfonate, N-hydroxysuccinimide 1-propanesulfonate, N-hydroxysuccinimide 2-propanesulfonate, N-hydroxysuccinimide 1-pentanesulfonate, N-hydroxysuccinimide p-toluenesulfonate, N-hydroxynaphthalimide methanesulfonate, and N-hydroxynaphthalimide benzenesulfonate are preferably used.
[0132] In the film-forming composition for lithography of the present embodiment, the content of the acid generator is not particularly limited, but is preferably 0 to 50 parts by mass, more preferably 0 to 40 parts by mass, when the total mass of the itaconimide compound in the film-forming material for lithography (preferably the total mass of the bisitaconimide compound and the addition polymerization type itaconimide resin) is taken as 100 parts by mass. By keeping the content within the above-mentioned preferred range, the crosslinking reaction tends to be enhanced, and the occurrence of the mixing phenomenon with the resist layer tends to be suppressed.
[0133] <Basic compounds> Furthermore, the composition for forming an underlayer film for lithography of this embodiment may contain a basic compound from the viewpoint of improving storage stability, etc.
[0134] The basic compound plays a role of a quencher against the acid to prevent a small amount of acid generated from the acid generator from proceeding with a crosslinking reaction. Examples of such basic compounds include, but are not limited to, primary, secondary, or tertiary aliphatic amines, mixed amines, aromatic amines, heterocyclic amines, nitrogen-containing compounds having a carboxyl group, nitrogen-containing compounds having a sulfonyl group, nitrogen-containing compounds having a hydroxyl group, nitrogen-containing compounds having a hydroxyphenyl group, alcoholic nitrogen-containing compounds, amide derivatives, or imide derivatives, as described in International Publication WO 2013 / 024779.
[0135] In the film-forming composition for lithography of the present embodiment, the content of the basic compound is not particularly limited, but is preferably 0 to 2 parts by mass, more preferably 0 to 1 part by mass, when the total mass of the itaconimide compounds in the film-forming material for lithography (preferably the total mass of the bisitaconimide compound and the addition polymerization type itaconimide resin) is taken as 100 parts by mass. By setting the content within the above-mentioned preferred range, the storage stability tends to be improved without excessively impairing the crosslinking reaction.
[0136] Furthermore, the film-forming composition for lithography of the present embodiment may contain known additives, including, but not limited to, ultraviolet absorbers, antifoaming agents, colorants, pigments, nonionic surfactants, anionic surfactants, cationic surfactants, and the like.
[0137] [Method of forming underlayer film and pattern for lithography] The underlayer film for lithography of the present embodiment is formed using the film-forming composition for lithography of the present embodiment.
[0138] The pattern formation method of the present embodiment also includes a step (A-1) of forming an underlayer film on a substrate using the film-forming composition for lithography of the present embodiment, a step (A-2) of forming at least one photoresist layer on the underlayer film, and, after the step (A-2), a step (A-3) of irradiating a predetermined region of the photoresist layer with radiation and performing development.
[0139] Further, another pattern forming method of this embodiment includes the following steps: (B-1) forming an underlayer film on a substrate using the lithography film forming composition of this embodiment; (B-2) forming an intermediate layer film on the underlayer film using a resist intermediate layer film material containing silicon atoms; (B-3) forming at least one photoresist layer on the intermediate layer film; (B-4) irradiating a predetermined area of the photoresist layer with radiation and developing it to form a resist pattern after the step (B-3); (B-5) etching the intermediate layer film using the resist pattern as a mask after the step (B-4), etching the underlayer film using the obtained intermediate layer film pattern as an etching mask, and etching the substrate using the obtained underlayer film pattern as an etching mask to form a pattern on the substrate. A conductive layer can also be formed on the pattern to form a circuit pattern.
[0140] The method for forming the underlayer film for lithography of the present embodiment is not particularly limited as long as it is formed from the composition for forming a film for lithography of the present embodiment, and a known method can be applied. For example, the composition for forming a film for lithography of the present embodiment is applied to a substrate by a known coating method or printing method such as spin coating or screen printing, and then the organic solvent is removed by volatilization, etc., to form the underlayer film.
[0141] When forming the underlayer film, it is preferable to bake it in order to suppress the occurrence of the mixing phenomenon with the upper resist layer and to promote the crosslinking reaction. In this case, the baking temperature is not particularly limited, but is preferably in the range of 80 to 450°C, more preferably 200 to 400°C. In addition, the baking time is also not particularly limited, but is preferably in the range of 10 to 300 seconds. The thickness of the underlayer film can be appropriately selected depending on the required performance, and is not particularly limited, but is usually preferably 30 to 20,000 nm, more preferably 50 to 15,000 nm, and even more preferably 50 to 1000 nm.
[0142] After forming an underlayer film on a substrate, it is preferable to form a silicon-containing resist layer thereon in the case of a two-layer process, or a single-layer resist made of a normal hydrocarbon thereon, and in the case of a three-layer process, a silicon-containing intermediate layer thereon, and further a silicon-free single-layer resist layer thereon. In this case, a known photoresist material can be used to form this resist layer.
[0143] As a silicon-containing resist material for a two-layer process, from the viewpoint of oxygen gas etching resistance, a positive photoresist material is preferably used which uses a silicon atom-containing polymer such as a polysilsesquioxane derivative or a vinylsilane derivative as a base polymer, and further contains an organic solvent, an acid generator, and if necessary, a basic compound, etc. Here, as the silicon atom-containing polymer, a known polymer used in this type of resist material can be used.
[0144] A polysilsesquioxane-based intermediate layer is preferably used as the silicon-containing intermediate layer for the three-layer process. By making the intermediate layer effective as an anti-reflection film, reflection tends to be effectively suppressed. For example, in a 193 nm exposure process, if a material containing many aromatic groups and having high substrate etching resistance is used as the underlayer film, the k value tends to be high and the substrate reflection tends to be high, but by suppressing reflection with the intermediate layer, the substrate reflection can be reduced to 0.5% or less. As an intermediate layer having such an anti-reflection effect, but not limited to the following, for 193 nm exposure, a polysilsesquioxane that is crosslinked by acid or heat and has a phenyl group or a light-absorbing group having a silicon-silicon bond introduced therein is preferably used.
[0145] An intermediate layer formed by a Chemical Vapour Deposition (CVD) method can also be used. As an intermediate layer produced by a CVD method that is highly effective as an anti-reflection film, for example, a SiON film is known, but is not limited to the following. In general, forming an intermediate layer by a wet process such as a spin coating method or screen printing has a simpler and more cost-effective advantage than the CVD method. The upper layer resist in the three-layer process may be either a positive type or a negative type, and the same resist as a commonly used single layer resist can be used.
[0146] Furthermore, the underlayer film of this embodiment can be used as an anti-reflection film for a normal single-layer resist or as an underlayer material for suppressing pattern collapse. Since the underlayer film of this embodiment has excellent etching resistance for underlayer processing, it can also be expected to function as a hard mask for underlayer processing.
[0147] When forming a resist layer using the photoresist material, a wet process such as spin coating or screen printing is preferably used, as in the case of forming the underlayer film. After applying the resist material by spin coating or the like, pre-baking is usually performed, and this pre-baking is preferably performed at 80 to 180° C. for 10 to 300 seconds. Thereafter, exposure is performed according to a conventional method, followed by post-exposure baking (PEB) and development to obtain a resist pattern. The thickness of the resist film is not particularly limited, but is generally preferably 30 to 500 nm, more preferably 50 to 400 nm.
[0148] The exposure light may be appropriately selected depending on the photoresist material used. In general, high energy rays having a wavelength of 300 nm or less, specifically, excimer lasers having wavelengths of 248 nm, 193 nm, and 157 nm, soft X-rays having wavelengths of 3 to 20 nm, electron beams, X-rays, and the like can be used.
[0149] The resist pattern formed by the above-mentioned method is prevented from collapsing due to the underlayer film of this embodiment, and therefore, by using the underlayer film of this embodiment, a finer pattern can be obtained and the exposure dose required to obtain the resist pattern can be reduced.
[0150] Next, etching is performed using the obtained resist pattern as a mask. Gas etching is preferably used for etching the lower layer film in the two-layer process. As the gas etching, etching using oxygen gas is suitable. In addition to oxygen gas, inert gases such as He and Ar, and CO, CO 2 , N.H. 3 , S.O. 2 , N 2 , NO 2 , H 2 It is also possible to add gases such as CO, CO without using oxygen gas. 2 , N.H. 3 , N 2 , NO 2 , H 2 Gas etching can also be performed using only the gas, and the latter gas is preferably used to protect the sidewalls of the pattern to prevent undercutting of the sidewalls.
[0151] On the other hand, gas etching is also preferably used for etching the middle layer in the three-layer process. The gas etching can be the same as that described in the two-layer process. In particular, the processing of the middle layer in the three-layer process is preferably performed using a fluorocarbon-based gas and a resist pattern as a mask. Then, as described above, the processing of the lower layer film can be performed by, for example, performing oxygen gas etching using the middle layer pattern as a mask.
[0152] Here, when an inorganic hard mask intermediate layer film is formed as the intermediate layer, a silicon oxide film, a silicon nitride film, or a silicon oxynitride film (SiON film) is formed by a CVD method, an ALD method, or the like. The method for forming the nitride film is not limited to the following, but for example, the method described in JP 2002-334869 A (Patent Document 6) and WO 2004 / 066377 (Patent Document 7) can be used. A photoresist film can be formed directly on such an intermediate layer film, but an organic anti-reflective coating (BARC) may be formed on the intermediate layer film by spin coating, and a photoresist film may be formed on the organic anti-reflective coating (BARC).
[0153] As the intermediate layer, a polysilsesquioxane-based intermediate layer is also preferably used. By making the resist intermediate layer film have an effect as an anti-reflection film, reflection tends to be effectively suppressed. The specific material of the polysilsesquioxane-based intermediate layer is not limited to the following, but for example, those described in JP-A-2007-226170 (Patent Document 8) and JP-A-2007-226204 (Patent Document 9) can be used.
[0154] The next etching of the substrate can also be carried out by a conventional method. For example, if the substrate is SiO 2 For SiN, etching can be performed mainly with fluorocarbon-based gases, while for p-Si, Al, and W, etching can be performed mainly with chlorine- or bromine-based gases. When etching a substrate with fluorocarbon-based gases, the silicon-containing resist of a two-layer resist process and the silicon-containing intermediate layer of a three-layer process are stripped at the same time as the substrate is processed. On the other hand, when etching a substrate with chlorine- or bromine-based gases, the silicon-containing resist layer or silicon-containing intermediate layer is stripped separately, and generally, dry etching stripping with fluorocarbon-based gases is performed after substrate processing.
[0155] The underlayer film of this embodiment is characterized by its excellent etching resistance to these substrates. The substrate can be appropriately selected from known substrates, and is not particularly limited, but includes Si, α-Si, p-Si, SiO 2, SiN, SiON, W, TiN, Al, etc. The substrate may be a laminate having a film to be processed (substrate to be processed) on a base material (support). Examples of such a film to be processed include Si, SiO 2 Examples of low-k films include various low-k films and stopper films thereof such as SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, and Al-Si, and usually, a film made of a material different from that of the base material (support) is used. The thickness of the substrate or film to be processed is not particularly limited, but is usually preferably about 50 to 1,000,000 nm, and more preferably 75 to 500,000 nm. EXAMPLES
[0156] The present invention will be described in more detail below with reference to Synthesis Examples, Examples, Production Examples, Reference Examples and Comparative Examples, but the present invention is not limited to these examples.
[0157] 1. Evaluation of heat resistance and solubility [Molecular weight] The molecular weight of the synthesized compound was measured by LC(GPC)-MS analysis using Water's Acquity UPLC / MALDI-Synapt HDMS.
[0158] [Heat resistance evaluation] Using an EXSTAR6000TG-DTA device manufactured by SII Nanotechnology, approximately 5 mg of the sample was placed in an unsealed aluminum container, and the sample was heated to 500°C at a heating rate of 10°C / min in a nitrogen gas (100 ml / min) flow to measure the amount of thermal weight loss. From a practical standpoint, the following A or B rating is preferable. Ratings of A or B indicate high heat resistance and can be applied to high-temperature baking. <Evaluation criteria> A: Thermal weight loss at 400℃ is less than 10% B: Thermal weight loss at 400℃ is 10% to 25% C: Thermal weight loss at 400℃ is more than 25%
[0159] [Evaluation of solubility] Propylene glycol monomethyl ether acetate (PGMEA) and a compound or resin were charged into a 50 ml screw bottle and stirred with a magnetic stirrer at 23° C. for 1 hour, after which the amount of the compound or resin dissolved in PGMEA was measured and the results were evaluated according to the following criteria. From a practical standpoint, the following S, A or B rating is preferable. If it is rated S, A or B, it has high storage stability in a solution state and can be fully applied to edge beat remover liquids (PGME / PGMEA mixed liquids) that are widely used in semiconductor microfabrication processes. If it is rated S, it is possible to produce an underlayer film-forming composition that has very excellent long-term storage stability and a long shelf life. <Evaluation criteria> S: 20% by mass or more A: 10% by mass or more and less than 20% by mass B: 5% by mass or more and less than 10% by mass C: Less than 5% by mass
[0160] Example 1A Itaconimide A was used alone as a bisitaconimide compound to prepare a film-forming material for lithography. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, evaluation of the solubility in PGMEA showed an excellent value of more than 20% by mass (evaluation S), and the obtained film-forming material for lithography was evaluated to have sufficient solubility. To 10 parts by mass of the film-forming material for lithography, 90 parts by mass of PGMEA was added as a solvent, and the mixture was stirred with a stirrer at room temperature for at least 3 hours or more to prepare a film-forming composition for lithography.
[0161] [ka]
[0162] Itaconimide A was synthesized with reference to "Synthesis of Bisitaconamic Acid and Isomer Bisimide Monomers", Galanti, A. V. et al., J. Polym. Sci: Poly, Chem. Ed, Vol. 20, pp. 233-239, 1982.
[0163] Example 1B Thermogravimetric measurements were similarly performed with itaconimide B replacing itaconimide A, and the thermal weight loss of the resulting film-forming material for lithography at 400°C was less than 10% (evaluation A). In addition, the solubility of itaconimide B in PGMEA was evaluated to be excellent at 20% by mass or more (evaluation S), and the resulting film-forming material for lithography was evaluated to have sufficient solubility.
[0164] [ka]
[0165] Itaconimide B was synthesized according to a standard method using the compound described in "Synthesis of bisitaconamic acid and isomeric bisimide monomers" by Galanti, A. V. et al., J. Polym. Sci: Poly, Chem. Ed (Journal of Polymer Science: Polymer Chemistry Edition), Vol. 20, pp. 233-239, 1982, as a raw material.
[0166] Example 1C: Synthesis of itaconimide C Itaconimide C was synthesized in the same manner as in Example 1 according to the standard method described above, except that 4,4'-diamino-3,3'dimethyldiphenylmethane (Tokyo Chemical Industry Co., Ltd.) was used instead of 4,4'-(4,4'-isopropylidenediphenyl-1,1'-diyldioxy)dianiline (Sigma-Aldrich Co., Ltd.) used as a raw material in Example 1. Using itaconimide C, a film-forming material for lithography was prepared in the same manner as in Example 1A.
[0167] [ka]
[0168] Example 1D: Synthesis of itaconimide D Itaconimide D was synthesized in the same manner as in Example 1 according to the standard method described above, except that a biphenyl aralkyl type polyaniline resin (product name: BAN, manufactured by Nippon Kayaku Co., Ltd.) was used instead of 4,4'-(4,4'-isopropylidenediphenyl-1,1'-diyldioxy)dianiline (manufactured by Sigma-Aldrich Co.) used as the raw material in Example 1. Using itaconimide D, a film-forming material for lithography was prepared in the same manner as in Example 1A.
[0169] [ka]
[0170] Example 2A A film-forming material for lithography was prepared by blending 10 parts by mass of itaconimide A and 0.1 parts by mass of 2,4,5-triphenylimidazole (TPIZ) as a crosslinking accelerator. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have sufficient solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of PGMEA was 90 parts by weight per 10 parts by weight of itaconimide A.
[0171] Example 3A A film-forming material for lithography was prepared by blending 10 parts by mass of itaconimide A and 0.1 parts by mass of triphenylphosphine (TPP) as a crosslinking accelerator. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have excellent solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0172] Example 4A A film-forming material for lithography was prepared by mixing 10 parts by mass of itaconimide A, 2 parts by mass of benzoxazine represented by the following formula (BF-BXZ; manufactured by Konishi Chemical Industry Co., Ltd.) as a crosslinking agent, and 0.1 parts by mass of 2,4,5-triphenylimidazole (TPIZ) as a crosslinking accelerator.
[0173] [ka]
[0174] Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have excellent solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0175] Example 5A A film-forming material for lithography was prepared by mixing 10 parts by mass of itaconimide A, 2 parts by mass of a biphenyl aralkyl type epoxy resin represented by the following formula (NC-3000-L; manufactured by Nippon Kayaku Co., Ltd.) as a crosslinking agent, and 0.1 parts by mass of TPIZ as a crosslinking accelerator.
[0176] [ka]
[0177] Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have excellent solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0178] Example 6A A film-forming material for lithography was prepared by mixing 10 parts by mass of itaconimide A, 2 parts by mass of diallyl bisphenol A cyanate (DABPA-CN; manufactured by Mitsubishi Gas Chemical Co., Ltd.) represented by the following formula as a crosslinking agent, and 0.1 parts by mass of 2,4,5-triphenylimidazole (TPIZ) as a crosslinking accelerator.
[0179] [ka]
[0180] Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 10% by mass or more and less than 20% by mass (evaluation A), and the obtained film-forming material for lithography was evaluated to have excellent solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0181] Example 7A A film-forming material for lithography was prepared by mixing 10 parts by mass of itaconimide A, 2 parts by mass of diallyl bisphenol A (BPA-CA; manufactured by Konishi Chemical Co., Ltd.) represented by the following formula as a crosslinking agent, and 0.1 parts by mass of 2,4,5-triphenylimidazole (TPIZ) as a crosslinking accelerator.
[0182] [ka]
[0183] Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have excellent solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0184] <Example 8A> A film-forming material for lithography was prepared by mixing 20 parts by mass of itaconimide A, 2 parts by mass of benzoxazine BF-BXZ represented by the above formula as a crosslinking agent, and 0.1 part by mass of TPIZ as a crosslinking accelerator. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have excellent solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 20 parts by mass of the bisitaconimide compound.
[0185] <Example 9A> A film-forming material for lithography was prepared by blending 10 parts by mass of itaconimide A, 2 parts by mass of benzoxazine BF-BXZ represented by the above formula as a crosslinking agent, and 0.1 part by mass of acid generator di-tert-butyldiphenyliodonium nonafluoromethanesulfonate (DTDPI; manufactured by Midori Chemical Co., Ltd.) to promote crosslinking. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have excellent solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0186] Example 10A A film-forming material for lithography was prepared by mixing 10 parts by mass of itaconimide A and 2 parts by mass of a diphenylmethane-type allylphenol resin represented by the following formula (APG-1; manufactured by Gun-ei Chemical Industry Co., Ltd.) as a crosslinking agent.
[0187] [ka]
[0188] Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have excellent solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0189] Example 11A 10 parts by mass of Itaconimide A and 2 parts by mass of a diphenylmethane type propenylphenol resin represented by the following formula (APG-2; manufactured by Gun-ei Chemical Industry Co., Ltd.) as a crosslinking agent were mixed to prepare a film-forming material for lithography.
[0190] [ka]
[0191] Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have excellent solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0192] <Example 12A> A film-forming material for lithography was prepared by blending 10 parts by mass of itaconimide A and 2 parts by mass of 4,4'-diaminodiphenylmethane (DDM; manufactured by Tokyo Chemical Industry Co., Ltd.) represented by the following formula as a crosslinking agent.
[0193] [ka]
[0194] Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have excellent solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0195] <Example 13A> Itaconimide A was used alone to prepare a film-forming material for lithography. As a result of thermogravimetry, the thermal weight loss of the obtained film-forming material for lithography at 400°C was less than 10% (evaluation A). In addition, as a result of evaluating the solubility in PGMEA, it was 5% by mass or more and less than 10% by mass (evaluation B), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 20 parts by mass of the film-forming material for lithography.
[0196] <Example 2B> A film-forming material for lithography was prepared in the same manner as in Example 2A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0197] <Example 3B> A film-forming material for lithography was prepared in the same manner as in Example 3A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0198] <Example 4B> A film-forming material for lithography was prepared in the same manner as in Example 4A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0199] <Example 5B> A film-forming material for lithography was prepared in the same manner as in Example 5A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0200] <Example 6B> A film-forming material for lithography was prepared in the same manner as in Example 6A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0201] <Example 7B> A film-forming material for lithography was prepared in the same manner as in Example 7A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0202] <Example 8B> A film-forming material for lithography was prepared in the same manner as in Example 8A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0203] <Example 9B> A film-forming material for lithography was prepared in the same manner as in Example 9A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0204] <Example 10B> A film-forming material for lithography was prepared in the same manner as in Example 10A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0205] <Example 11B> A film-forming material for lithography was prepared in the same manner as in Example 11A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0206] <Example 12B> A film-forming material for lithography was prepared in the same manner as in Example 12A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0207] <Example 13B> A film-forming material for lithography was prepared in the same manner as in Example 13A, except that Itaconimide B was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 20 parts by mass of the itaconimide compound.
[0208] Example 2C A film-forming material for lithography was prepared in the same manner as in Example 2A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0209] Example 3C A film-forming material for lithography was prepared in the same manner as in Example 3A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0210] <Example 4C> A film-forming material for lithography was prepared in the same manner as in Example 4A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0211] <Example 5C> A film-forming material for lithography was prepared in the same manner as in Example 5A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0212] <Example 6C> A film-forming material for lithography was prepared in the same manner as in Example 6A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0213] <Example 7C> A film-forming material for lithography was prepared in the same manner as in Example 7C, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0214] <Example 8C> A film-forming material for lithography was prepared in the same manner as in Example 8A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0215] <Example 9C> A film-forming material for lithography was prepared in the same manner as in Example 9A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0216] <Example 10C> A film-forming material for lithography was prepared in the same manner as in Example 10A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0217] <Example 11C> A film-forming material for lithography was prepared in the same manner as in Example 11A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0218] <Example 12C> A film-forming material for lithography was prepared in the same manner as in Example 12A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0219] <Example 13C> A film-forming material for lithography was prepared in the same manner as in Example 13A, except that Itaconimide C was used instead of Itaconimide A. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 20 parts by mass of the itaconimide compound.
[0220] Example 2D A film-forming material for lithography was prepared in the same manner as in Example 2B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0221] Example 3D A film-forming material for lithography was prepared in the same manner as in Example 3B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0222] <Example 4D> A film-forming material for lithography was prepared in the same manner as in Example 4B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0223] <Example 5D> A film-forming material for lithography was prepared in the same manner as in Example 5B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0224] <Example 6D> A film-forming material for lithography was prepared in the same manner as in Example 6B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0225] <Example 7D> A film-forming material for lithography was prepared in the same manner as in Example 7B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0226] <Example 8D> A film-forming material for lithography was prepared in the same manner as in Example 8B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0227] <Example 9D> A film-forming material for lithography was prepared in the same manner as in Example 9B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0228] <Example 10D> A film-forming material for lithography was prepared in the same manner as in Example 10B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0229] <Example 11D> A film-forming material for lithography was prepared in the same manner as in Example 11B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0230] <Example 12D> A film-forming material for lithography was prepared in the same manner as in Example 12B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 10 parts by mass of the itaconimide compound.
[0231] <Example 13D> A film-forming material for lithography was prepared in the same manner as in Example 13B, except that Itaconimide D was used instead of Itaconimide B. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 20% by mass or more (evaluation S), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. A solvent was added to the film-forming material for lithography, and the mixture was stirred at room temperature for at least 3 hours with a stirrer to prepare a film-forming composition for lithography. PGMEA was used as the solvent, and the amount of the solvent was 90 parts by mass relative to 20 parts by mass of the itaconimide compound.
[0232] <Reference example 1> A film-forming material for lithography was prepared by using 10 parts by mass of a phenol compound (BisN-1) represented by the following formula described in WO 2013 / 024779 alone. Thermogravimetric analysis showed that the thermal weight loss of the obtained film-forming material for lithography at 400° C. was less than 10% (evaluation A). In addition, the solubility in PGMEA was evaluated to be 10% by mass or more and less than 20% by mass (evaluation A), and the obtained film-forming material for lithography was evaluated to have the necessary solubility. To 10 parts by mass of the film-forming material for lithography, 90 parts by mass of PGMEA was added as a solvent, and the mixture was stirred with a stirrer at room temperature for at least 3 hours or more to prepare a film-forming composition for lithography.
[0233] [ka]
[0234] 2.Membrane performance evaluation <Examples 1 to 13, Comparative Examples 1 to 2> Lithography film-forming compositions corresponding to Examples 1A to 13A, 1B to 13B, 1C to 13C, 1D to 13D, and Comparative Examples 1 to 2 were prepared so as to have the compositions shown in Tables 1-1 to 1-4. Next, the lithography film-forming compositions were spin-coated on a silicon substrate, and then baked at 240°C for 60 seconds and then at 400°C for 120 seconds to prepare underlayer films with a thickness of 200 nm. The film thickness reduction rate (%) was calculated from the difference in film thickness before and after baking at 400°C to evaluate the film heat resistance of each underlayer film. Then, the etching resistance was evaluated under the conditions shown below. In addition, the embedding ability into a stepped substrate and the flatness were evaluated under the conditions shown below.
[0235] <Examples 14 and 15> Lithography film-forming compositions corresponding to Examples 14A to 14D and 15A to 15D were prepared so as to have the compositions shown in Tables 2-1 and 2-2. The lithography film-forming compositions were then spin-coated onto a silicon substrate, which was then baked at 110°C for 60 seconds to remove the solvent from the coating, and then exposed to a high-pressure mercury lamp with an accumulated exposure dose of 600 mJ / cm. 2 The resulting coating was then cured for 20 seconds and baked at 400°C for 120 seconds to produce an underlayer film with a thickness of 200 nm. The film thickness reduction rate (%) was calculated from the difference in film thickness before and after baking at 400°C to evaluate the film heat resistance of each underlayer film. The etching resistance was then evaluated under the conditions shown below. The embedding ability into a stepped substrate and flatness were also evaluated under the conditions shown below.
[0236] <Examples 16 and 17 and Reference Example 1> Lithography film-forming compositions corresponding to Examples 16A to 16D, 17A to 17D, and Reference Example 1 were prepared so as to have the compositions shown in Tables 3-1 and 3-2. Next, the lithography film-forming compositions were spin-coated on a silicon substrate, which was then baked at 110° C. for 60 seconds to remove the solvent from the coating, and then exposed to an accumulated exposure dose of 600 mJ / cm 2 using a high-pressure mercury lamp. 2 The resulting coating was then cured for 20 seconds and baked at 400°C for 120 seconds to produce an underlayer film with a thickness of 200 nm. The film thickness reduction rate (%) was calculated from the difference in film thickness before and after baking at 400°C to evaluate the film heat resistance of each underlayer film. The etching resistance was then evaluated under the conditions shown below. The embedding ability into a stepped substrate and flatness were also evaluated under the conditions shown below.
[0237] [Evaluation of film heat resistance] <Evaluation criteria> S: Film thickness reduction rate before and after 400℃ baking ≦10% A: Film thickness reduction rate before and after 400℃ baking ≦15% B: Film thickness reduction rate before and after 400℃ baking ≦20% C: Film thickness reduction rate before and after 400℃ baking > 20%
[0238] [Etching test] Etching equipment: Samco International RIE-10NR Output: 50W Pressure: 4Pa Time: 2 minutes Etching Gas CF 4 Gas flow rate: O 2 Gas flow rate = 5:15 (sccm)
[0239] [Evaluation of etching resistance] The etching resistance was evaluated according to the following procedure. First, a novolac underlayer film was prepared under the same conditions as in Example 1, except that a novolac (PSM4357 manufactured by Gun-ei Chemical Co., Ltd.) was used instead of the lithography film-forming material in Example 1, and the drying temperature was set to 110° C. Then, the above-mentioned etching test was performed on this novolac underlayer film, and the etching rate was measured. Next, the etching test was carried out in the same manner as above for the underlayer films of Example, Comparative Examples 1 and 2, and Reference Example 1, and the etching rates were measured. The etching resistance was evaluated according to the following evaluation criteria, based on the etching rate of the novolac underlayer film: From a practical viewpoint, the following S rating is particularly preferable, and A and B ratings are more preferable. <Evaluation criteria> S: Etching rate is less than -30% compared to the underlayer of novolac A: The etching rate is between -30% and -20% compared to the novolac underlayer. B: The etching rate is -20% or more to less than -10% compared to the underlayer film of novolac. C: The etching rate is -10% or more and 0% or less compared to the underlayer film of novolac.
[0240] [Evaluation of board step filling ability] The embedding ability into a stepped substrate was evaluated according to the following procedure. The composition for forming an underlayer film for lithography was applied to a SiO 2A 90 nm underlayer film was formed by coating the film on a substrate and baking for 60 seconds at 240° C. A cross section of the film obtained was cut out and observed under an electron beam microscope to evaluate its embedding ability into stepped substrates. <Evaluation criteria> A: 60nm line and space SiO 2 The lower layer film is embedded into the uneven parts of the substrate without any defects. C: 60 nm line and space SiO 2 There are defects in the uneven parts of the substrate, and the underlayer film is not embedded.
[0241] [Flatness evaluation] SiO2 containing a mixture of trenches (aspect ratio: 1.5) with a width of 100 nm, a pitch of 150 nm, and a depth of 150 nm, and trenches (open space) with a width of 5 μm and a depth of 180 nm. 2 The film-forming compositions obtained above were applied onto the step substrate. Then, the substrate was baked at 240° C. for 120 seconds in an air atmosphere to form a resist underlayer film having a thickness of 200 nm. The shape of the resist underlayer film was observed with a scanning electron microscope (Hitachi High-Technologies Corporation's "S-4800"), and the difference (ΔFT) between the maximum and minimum film thicknesses of the resist underlayer film on the trench or space was measured. <Evaluation criteria> S: ΔFT<10nm (best flatness) A:10nm≦ΔFT<20nm (good flatness) B: 20nm≦ΔFT<40nm (flatness is good) C:40nm≦ΔFT (poor flatness)
[0242] [Table 1-1]
[0243] [Table 1-2]
[0244] [Table 1-3]
[0245] [Table 1-4]
[0246] [Table 2-1]
[0247] [Table 2-2]
[0248] [Table 3-1]
[0249] [Table 3-2]
[0250] <Example 18> The film-forming composition for lithography in Example 1A was mixed with a SiO 2 The substrate was coated with the solution and baked at 240°C for 60 seconds and then at 400°C for 120 seconds to form an underlayer film with a thickness of 70 nm. An ArF resist solution was coated on the underlayer film and baked at 130°C for 60 seconds to form a photoresist layer with a thickness of 140 nm. The ArF resist solution was prepared by blending 5 parts by mass of the compound of the following formula (22), 1 part by mass of triphenylsulfonium nonafluoromethanesulfonate, 2 parts by mass of tributylamine, and 92 parts by mass of PGMEA. The compound of the following formula (22) was prepared as follows. That is, 4.15 g of 2-methyl-2-methacryloyloxyadamantane, 3.00 g of methacryloyloxy-γ-butyrolactone, 2.08 g of 3-hydroxy-1-adamantyl methacrylate, and 0.38 g of azobisisobutyronitrile were dissolved in 80 mL of tetrahydrofuran to obtain a reaction solution. The reaction solution was polymerized for 22 hours under a nitrogen atmosphere at a reaction temperature of 63° C., and then the reaction solution was dropped into 400 mL of n-hexane. The resin thus produced was coagulated and purified, and the resulting white powder was filtered and dried overnight at 40° C. under reduced pressure to obtain a compound represented by the following formula.
[0251] [ka]
[0252] In the formula (22), the numbers 40, 40, and 20 indicate the ratio of each constituent unit, and do not indicate a block copolymer.
[0253] The photoresist layer was then exposed to light using an electron beam lithography system (ELS-7500, 50 keV, manufactured by Elionix), baked at 115°C for 90 seconds (PEB), and developed with a 2.38% by mass aqueous solution of tetramethylammonium hydroxide (TMAH) for 60 seconds to obtain a positive resist pattern. The evaluation results are shown in Table 4.
[0254] <Example 19> A positive resist pattern was obtained in the same manner as in Example 18, except that the composition for forming an underlayer film for lithography in Example 1B was used instead of the composition for forming an underlayer film for lithography in Example 1A. The evaluation results are shown in Table 4.
[0255] <Comparative Example 3> The photoresist layer was formed on the SiO 2 A positive resist pattern was obtained by directly forming the resist on the substrate. The evaluation results are shown in Table 4.
[0256] [evaluation] For each of Examples 18 to 19 and Comparative Example 3, the shapes of the obtained resist patterns of 55 nmL / S (1:1) and 80 nmL / S (1:1) were observed using an electron microscope (S-4800) manufactured by Hitachi, Ltd. Regarding the shape of the resist pattern after development, those without pattern collapse and with good rectangularity were evaluated as good, and those without were evaluated as bad. Furthermore, as a result of the observation, the minimum line width without pattern collapse and with good rectangularity was used as an index of evaluation as resolution. Furthermore, the minimum amount of electron beam energy capable of drawing a good pattern shape was used as an index of evaluation as sensitivity.
[0257] [Table 4]
[0258] As is clear from Table 4, it was confirmed that Examples 39 to 40, which used the film-forming composition for lithography of this embodiment containing a bisitaconimide compound, were significantly superior in both resolution and sensitivity compared to Comparative Example 3. In addition, it was confirmed that the resist pattern shape after development was free of pattern collapse and had good rectangularity. Furthermore, from the difference in the resist pattern shape after development, it was shown that the underlayer films of Examples 39 to 40 obtained from the film-forming composition for lithography of Examples 5 to 8 had good adhesion to the resist material.
[0259] <Examples 20 to 23> The lithography film-forming compositions in Examples 1A, 1B, 2A, and 3A were each coated with a SiO 2 The coating was applied to a substrate and baked at 240°C for 60 seconds and then at 400°C for 120 seconds to form a 70 nm thick underlayer film. The film surface was then observed with an optical microscope to check for defects. The evaluation results are shown in Table 5.
[0260] <Comparative Example 4> The film surface was observed with an optical microscope to check for the presence or absence of defects in the same manner as in Example 20, except that BMI (manufactured by Daiwa Chemical Industry Co., Ltd.) was used instead of Itaconimide A. The evaluation results are shown in Table 5.
[0261] [ka]
[0262] <Comparative Example 5> The film surface was observed with an optical microscope to check for the presence or absence of defects in the same manner as in Example 21, except that BMI-80 (manufactured by Daiwa Chemical Industry Co., Ltd.) was used instead of Itaconimide B. The evaluation results are shown in Table 5.
[0263] [ka]
[0264] <Evaluation criteria> A: No defects B: Almost no defects C: Defective The term "defect" refers to the presence of foreign matter that is confirmed when observing the film surface with an optical microscope.
[0265] [Table 5]
[0266] As is clear from Table 5, it was confirmed that in Examples 20 to 23, which used the film-forming composition for lithography of this embodiment containing a bisitaconimide compound, films with reduced defects were obtained, compared to Comparative Examples 4 and 5, which contained a bismaleimide compound. The reason for this is unclear, but it is presumed that the bisitaconimide compound has higher solubility stability in a solvent than the bismaleimide compound, or is less likely to undergo self-reaction between compounds, making it less likely to generate fine particles that cause defects.
[0267] The lithography film-forming material of this embodiment has relatively high heat resistance, relatively high solvent solubility, excellent embedding properties in step substrates and film flatness, and is applicable to wet processes. Therefore, the lithography film-forming composition containing the lithography film-forming material can be widely and effectively used in various applications requiring these properties. In particular, the present invention can be particularly effectively used in the fields of lithography underlayer films and multilayer resist underlayer films.
Claims
1. A group of the following formula (0): 【Chemistry 1】 (In formula (0), R 01 , R 02 , R 03 are each independently a hydrogen atom, a linear or branched alkyl group having 1 to 18 carbon atoms, a cyclic alkyl group having 3 to 18 carbon atoms, an aryl group having 6 to 18 carbon atoms, an aralkyl group having 7 to 30 carbon atoms, or an alkylaryl group having 7 to 30 carbon atoms. A film-forming material for lithography, comprising a compound having the formula: The compound having a group of the formula (0) is a bisitaconimide compound represented by the following formula (1A): It is an addition polymerization type itaconimide resin represented by the following formula (2) or the following formula (3): Film-forming material for lithography. 【Chemistry 2】 (In formula (1A), R 01 , R 02 , R 03 is defined as above, Each X is independently a single bond, —O—, or —CH 2 -, -C(CH 3 ) 2 -, -CO-, -C(CF 3 ) 2 -, -CONH- or -COO-; A is a single bond, an oxygen atom, or a divalent hydrocarbon group having 1 to 80 carbon atoms which may contain a heteroatom; R 1 each independently represents a group having 0 to 30 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, Each m1 is independently an integer of 0 to 4. 【Chemistry 3】 (In formula (2), R 01 , R 02 , R 03 is defined as above, R 2 each independently represents a group having 0 to 10 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, m2 each independently represents an integer of 0 to 3; m2' is independently an integer of 0 to 4, n is an integer from 1 to 4. 【Chemistry 4】 (In formula (3), R 01 , R 02 , R 03 is defined as above, R 3 and R 4 each independently represents a group having 0 to 10 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, m3 each independently represents an integer of 0 to 4, m4 is independently an integer of 0 to 4, n is an integer from 1 to 4.
2. The divalent hydrocarbon group having 1 to 80 carbon atoms which may contain a heteroatom in A is -(CH 2 ) p --, --CH 2 C (CH 3 ) 2 CH 2 -, -(C(CH 3 ) 2 ) p -, -(O(CH 2 ) q ) p -, -(O(C 6 H 4 )) p - or any of the following groups: 【Chemistry 5】 Y is a single bond, -O-, -CH 2 -, -C(CH 3 ) 2 -, -C(CF 3 ) 2 - or any of the following groups: 【Chemistry 6】 p is an integer from 1 to 20; Each q is independently an integer from 1 to 4; The film-forming material for lithography according to claim 1 .
3. The film-forming material for lithography according to claim 1 or 2, further comprising a crosslinking agent.
4. 4. The film-forming material for lithography according to claim 3, wherein the crosslinking agent is at least one selected from the group consisting of a phenol compound, an epoxy compound, a cyanate compound, an amino compound, a benzoxazine compound, a melamine compound, a guanamine compound, a glycoluril compound, a urea compound, an isocyanate compound, and an azide compound.
5. The film-forming material for lithography according to claim 3 or 4, wherein the crosslinking agent has at least one allyl group.
6. 6. The film-forming material for lithography according to claim 3, wherein the content of the crosslinking agent is 0.1 to 100 parts by mass, based on 100 parts by mass of the total amount of the compound having a group of formula (0).
7. The film-forming material for lithography according to any one of claims 1 to 6, further comprising a crosslinking promoter.
8. 8. The film-forming material for lithography according to claim 7, wherein the crosslinking accelerator is at least one selected from the group consisting of amines, imidazoles, organic phosphines, and Lewis acids.
9. 9. The film-forming material for lithography according to claim 7 or 8, wherein the content of the crosslinking accelerator is 0.1 to 5 parts by mass, based on 100 parts by mass of the total amount of the compound having a group of formula (0).
10. The film-forming material for lithography according to any one of claims 1 to 9, further comprising a radical polymerization initiator.
11. 11. The film-forming material for lithography according to claim 10, wherein the radical polymerization initiator is at least one selected from the group consisting of a ketone-based photopolymerization initiator, an organic peroxide-based polymerization initiator, and an azo-based polymerization initiator.
12. 12. The film-forming material for lithography according to claim 10, wherein the content of the radical polymerization initiator is 0.05 to 25 parts by mass, relative to 100 parts by mass of the total amount of the compound having a group of formula (0).
13. A film-forming composition for lithography, comprising the film-forming material for lithography according to any one of claims 1 to 12 and a solvent.
14. The film-forming composition for lithography according to claim 13 , further comprising an acid generator.
15. The composition for forming a film for lithography according to claim 13 or 14, wherein the film for lithography is an underlayer film for lithography.
16. An underlayer film for lithography, formed using the film-forming composition for lithography according to claim 15 .
17. A step of forming an underlayer film on a substrate using the film-forming composition for lithography according to claim 15; forming at least one photoresist layer on the underlayer film; and exposing predetermined areas of the photoresist layer to radiation and developing; A method for forming a resist pattern comprising the steps of:
18. A step of forming an underlayer film on a substrate using the film-forming composition for lithography according to claim 15; forming an intermediate layer film on the underlayer film using a resist intermediate layer film material containing silicon atoms; forming at least one photoresist layer on the intermediate layer film; irradiating predetermined areas of the photoresist layer with radiation and developing to form a resist pattern; a step of etching the intermediate layer film using the resist pattern as a mask; a step of etching the underlayer film using the obtained intermediate layer film pattern as an etching mask; and a step of forming a pattern on the substrate by etching the substrate using the obtained underlayer film pattern as an etching mask; A pattern forming method comprising the steps of:
19. A step of dissolving a compound having a group of formula (0) according to claim 1 or 2 in a solvent to obtain an organic phase; a first extraction step of contacting the organic phase with an acidic aqueous solution to extract impurities in the compound; Including, The method for purification, wherein the solvent used in the step of obtaining the organic phase comprises a solvent that is optionally immiscible with water.
20. The acidic aqueous solution is a mineral acid aqueous solution or an organic acid aqueous solution, The mineral acid aqueous solution contains one or more acids selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid, The purification method according to claim 19, wherein the aqueous organic acid solution contains one or more acids selected from the group consisting of acetic acid, propionic acid, oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, tartaric acid, citric acid, methanesulfonic acid, phenolsulfonic acid, p-toluenesulfonic acid, and trifluoroacetic acid.
21. The purification method according to claim 19 or 20, wherein the water-immiscible solvent is one or more solvents selected from the group consisting of toluene, 2-heptanone, cyclohexanone, cyclopentanone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, and ethyl acetate.
22. The purification method according to any one of claims 19 to 21, further comprising a second extraction step of contacting the organic phase with water after the first extraction step to extract impurities in the compound having a group of formula (0).
23. An addition polymerization type itaconimide resin represented by the following formula (2) or the following formula (3): 【Chemistry 7】 (In formula (2), R 01 , R 02 , R 03 each independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 18 carbon atoms, a cyclic alkyl group having 3 to 18 carbon atoms, an aryl group having 6 to 18 carbon atoms, an aralkyl group having 7 to 30 carbon atoms, or an alkylaryl group having 7 to 30 carbon atoms, R 2 each independently represents a group having 0 to 10 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, m2 each independently represents an integer of 0 to 3; m2' is independently an integer of 0 to 4, n is an integer from 1 to 4. 【Chemistry 8】 (In formula (3), R 01 , R 02 , R 03 each independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 18 carbon atoms, a cyclic alkyl group having 3 to 18 carbon atoms, an aryl group having 6 to 18 carbon atoms, an aralkyl group having 7 to 30 carbon atoms, or an alkylaryl group having 7 to 30 carbon atoms, R 3 and R 4 each independently represents a group having 0 to 10 carbon atoms (excluding hydrogen atoms) which may contain a heteroatom, m3 each independently represents an integer of 0 to 4, m4 is independently an integer of 0 to 4, n is an integer from 1 to 4.
24. R 2 , R 3 and R 4 The addition polymerization type itaconimide resin according to claim 23, wherein is an alkyl group.
25. 25. The addition polymerization type itaconimide resin according to claim 23 or 24, wherein the heteroatom is selected from the group consisting of oxygen, fluorine, and silicon.
26. The addition polymerization itaconimide resin according to any one of claims 23 to 25, wherein the heteroatom is oxygen.
Citation Information
Patent Citations
Method and device for forming silicon nitride film, and method for preprocessing of cleaning thereof
JP2002334869A
Base layer film forming material for multilayer resist process, and wiring formation method using the same
JP2004177668A
Resist underlayer film material and pattern forming method
JP2004271838A
Resist underlayer film material and pattern forming method
JP2005250434A
Ink composition
JP2007051196A